Santora, Mamie (audio interview #1 of 2) - Santora, Mamie (b. 06/25/1888 - d. 4/1/1984); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - Mamie Santora was referred to the Feminist History Research Project by the ACWA, and arrangements were made to interview her during a research trip by Gluck to Washington, D.C. Santora was living in a neat, bungalow in a working class neighborhood of Baltimore. Because she had been recommended by the union, at the time of the first interview, she mistakenly believed that I was with the union. As a result, although she was friendly and cordial, she was guarded in her discussions about the fate of the Women's Locals and the women's desire to form a Women's Bureau or Department in the ACWA. TOPICS - family history; work experiences; education; union organizing; working conditions; chairlady role; strike; Dorothy Jacobs Bellanca; Sidney Hillman; Bessie Abramovitz Hillman; appointment to position on Joint Board in Baltimore; election to ACWA General Executive Board; and formation of ACWA;1920 ACWA National Convention; election to ACWA General Executive Board; Baltimore Women's Local (Local 70); position as secretary-treasurer of Baltimore Joint Board; organizing drives in Philadelphia and New England; Dorothy Jacobs Bellanca; Sidney Hillman; resolution for women's department, 1924; Women's Locals; working conditions in garment shops and physical effects on women; labor courses education at Bryn Mawr and John Hopkins University; and attitude towards ACWA wages and pension plans; 5/20/1975